2016
DOI: 10.3892/ol.2016.4110
|View full text |Cite
|
Sign up to set email alerts
|

AURKA promotes cell migration and invasion of head and neck squamous cell carcinoma through regulation of the AURKA/Akt/FAK signaling pathway

Abstract: Abstract. The present study aimed to investigate the mechanism by which Aurora kinase A (AURKA) promotes cell migration and invasion in head and neck squamous cell carcinoma (HNSCC). Transwell assays were performed to investigate the cell migration and invasion abilities of AURKA, whilst western blotting was used to analyze the protein expression in FaDu and Hep2 cells, each treated with pharmacological inhibitors. Following the inhibition of AURKA, Akt and focal adhesion kinase (FAK), the migration and invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
1
22
0
2
Order By: Relevance
“…Our findings further confirmed the association of the reduced expression of AURKA with the invasiveness of BC. Besides, AURKA phosphorylation activated the microtubule-associated oncogene known as the targeting protein for xenopus kinesin-like protein 2 (TPX2 ), which contributes to the migration and invasion of cancer cells through the Akt and focal adhesion kinase signaling (Yang et al, 2015;Wu et al, 2016). As shown in this research, the reduced expression of AURKA was detectable in the peripheral blood of cancer patients.…”
Section: Resultssupporting
confidence: 58%
“…Our findings further confirmed the association of the reduced expression of AURKA with the invasiveness of BC. Besides, AURKA phosphorylation activated the microtubule-associated oncogene known as the targeting protein for xenopus kinesin-like protein 2 (TPX2 ), which contributes to the migration and invasion of cancer cells through the Akt and focal adhesion kinase signaling (Yang et al, 2015;Wu et al, 2016). As shown in this research, the reduced expression of AURKA was detectable in the peripheral blood of cancer patients.…”
Section: Resultssupporting
confidence: 58%
“…AKT is activated by phosphorylation, and it is able to phosphorylate and activate downstream substrates, stimulating cell migration [ 50 ]. Besides the conventional function of AuA in the mitotic regulation of the cell cycle, the non-mitotic roles of AuA in cell migration and tumorigenesis have attracted considerable attention recently [ 16 , 36 , 51 , 52 ]. Consistent with previous reports, our study demonstrated that ARD1-mediated AuA acetylation induces the expression of phosphorylated AKT to activate cell migration, and it provides a new regulatory mechanism by which AuA facilitates cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the overexpression of CENPF and TOP2A is associated with poor prognosis in cancers, including HCC [49,50] . AURKA has been confirmed as an oncogene in cancer development, which promotes tumor development by promoting a variety of biological functions, including cell proliferation, migration, invasion, EMT and cancer stem cell behaviors [51,52] .…”
Section: Discussionmentioning
confidence: 99%